HiggsBounds-5: testing Higgs sectors in the LHC 13 TeV Era - Bechtle, Philip; Dercks, Daniel; Heinemeyer, Sven; Klingl, Tobias; Stefaniak, Tim; Weiglein, Georg; Wittbrodt, Jonas (European Physical Journal C, 2020)
We describe recent developments of the public computer code HiggsBounds. In particular, these include the incorporation of LHC Higgs search results from Run 2 at a center-of-mass energy of 13 TeV, and an updated and extended framework for the theoretical input that accounts for improved Higgs cross section and branching ratio predictions and new search channels. We furthermore discuss an improved method used in HiggsBounds to approximately reconstruct the exclusion likelihood for LHC searches for non-standard Higgs bosons decaying to τ τ final states. We describe in detail the new and updated functionalities of the new version HiggsBounds-5.